Corporate Social Responsibility Sebagai Promosi Perseroan Terbatas - Yusuf, Chandra; Purwaningsih, Endang (Jurnal Hukum & Pembangunan, 2019)
The application of Corporate Social Responsibility (CSR) and Fiduciary Duty in Law No. 40 of 2007 concerning Limited Liability Companies creates a conflict of interest. The problem that arises is the placement of CSR in the company's income statement that will reduce the company's dividend distribution. This violates the principle of "fiduciary duty". Directors of Limited Liability Company must maximize shareholder prosperity. So far, CSR is considered a social activity. To avoid conflicts of interest, CSR must be classified into a promotional account in the financial statements, especially the Balance Sheet. The method used to assess CSR refers to the effects of promotions on investors. Therefore, CSR is not separated from the account in the company's operational costs. Article 1 Paragraph (3) The Limited Liability Company Law No. 40 of 2007 concerning Limited Liability Companies needs to be revised and does not refer to social interests, but the commercial interests of shareholders.